Analisis Ketersediaan Air Waduk Gadjah Mungkur dengan Adanya Pembangunan Intake dan Jaringan Pipa Trasmisi Wosusokas - Cantik, B.K.P.; Fitriana, I.R.; Diandra, N.; Valentino, S.; Tambing, A.K. (Civil Engineering Department, Tadulako University, 2021)
Gadjah Mungkur Reservoir is one of the multipurpose reservoirs built by damming the flow of the Bengawan Solo River. The Gadjah Mungkur Reservoir has existed for a long time with the main purpose of controlling flooding, but over time, this reservoir is also useful as a hydropower plant, irrigation, and also to meet the raw water needs of Wonogiri City. The potential of the Gadjah Mungkur Reservoir itself in meeting the needs of drinking water is an essential function in the people’s life around the reservoir. Therefore, the expansion of the scope of providing drinking water can be used to develop the potential of the Gadjah Mungkur Reservoir. This coverage expansion was realized through the construction of the Wosusokas intake and transmission pipeline network to drinking water receiving areas, namely Wonogiri, Sukoharjo, Solo, and Karanganyar, with service coverage of drinking water access resepectively ±78,38, ±70,97%, ±81,85%, and ±70,97%. This study aims to analyze the water availability of the Gadjah Mungkur Reservoir with additional coverage for drinking water services. The method used is a simple reservoir routing calculation by processing secondary data obtained in the form of inflow, outflow, and reservoir storage characteristics. The results of the analysis show that elevation variations with the construction of the Wosusokas intake and transmission pipeline have an annual average of +132,56 m in 2017, with a reservoir storage volume reaching 216,27 MCM and +134,29 m in 2018, with a reservoir storage volume reaching 284,92 MCM. However, there are some elevation values that exceed +138,0 m, namely at February to March 2018. However, overall, the results of the analysis show that the Wosusokas construction can increase the potential utilization of the Gadjah Mungkur Reservoir without endangering the reservoir with water level fluctuations that can still be controlled and in accordance with the regulation of reservoir water level.